Decolorization of naphthol batik effluents using immobilized enzyme of Aspergillus sp. GPN and zeolite‐activated carbon in a wastewater treatment plant (WWTP) - Ratna Stia Dewi; Putri Ramadani; Saefuddin Aziz (Indonesian Journal of Biotechnology, 2026)
Industrial batik wastewater containing naphthol dyes is persistent, dark in color, and contains complex organic compounds that have the potential to pollute aquatic environments. Conventional physicochemical treatment methods are often ineffective in degrading resistant aromatic compounds and involve high operational costs, thus necessitating alternative approaches that are more environmentally friendly and sustainable. This study evaluates the effectiveness of extracellular enzymes from Aspergillus sp. immobilized in a chitosan matrix, combined with a zeolite‐activated carbon adsorbent medium, in the decolorization of naphthol dye wastewater in a treatment system using a wastewater treatment plant. The enzymes were obtained from liquid cultures and subsequently immobilized using an encapsulation method in chitosan beads. The treatment process was conducted over 72 hours of incubation, with observations of the percentage of dye decolorization. The results show that the combination of immobilized enzymes and zeolite‐activated carbon provides a significant increase in decolorization efficiency compared to single treatments. The highest decolorization was obtained in black‐blue naphthol waste, with an efficiency of 86.94% after 72 hours of incubation. These findings indicate that a combination system of immobilized biocatalysts and adsorbents has the potential to become a more stable and effective alternative technology for batik waste treatment. The approach opens up opportunities for the development of more applicable and sustainable enzyme‐based waste treatment systems on an industrial scale.